PENINGKATAN KINERJA MENGAJAR GURU MELALUI PENERAPAN MANAJEMEN PENGETAHUAN DAN PENGEMBANGAN KAPASITAS GURU MADRASAH ALIYAH DI KOTA BANDUNG - -, Suryadi; Permana, Johar (Universitas Pendidikan Indonesia, 2017)
This study aimed to describe and analyze the knowledge management and capacity development of teachers Madrasah Aliyah in Bandung. Analytic descriptive method with quantitative approach used in this study on 225 respondents. The result: There is a significant effect simultaneously knowledge management, capacity building of teachers to the teacher's teaching performance MA in Bandung, knowledge management and capacity development of teachers are in the category enough. Personal dimension, procedures and technologies with category enough. Dimension policy, management, quality assurance, impact category enough.